El sistema de retención en la fuente del impuesto a las ventas entre Colombia y Chile (2013)
This work aims to establish similarities and differences between the Withholding Tax on Sales of Colombia and Chile, as a complementary part to the description and the state of art of national tax called Sales Tax is collected partly through the system of withholding, and this becomes important because of the possibility of exercising the application of concepts, not only the area of research that are in the curriculum of the program, but to deepen the area of tax and strengthen knowledge.